Yaakov Katz and Amir Bohbot, The Weapon Wizards: How Israel Became a High-Tech Military Superpower - Ms. Afeera Firdous (CISS Insight Journal, 2017)
The book’s main focus is technological advancement in Israel’s military industry. It has eight chapters and each chapter discusses a specific military aspect in the story of Israel’s technological revolution. All the chapters are based on extensive interviews of relevant people belonging to different military backgrounds. In the introduction, the authors point out Israel’s scarce natural resources, and that its only asset is human resource. In this situation, the country looked for some national trait which could be helpful to the newly born state to survive and prosper. A culture of innovation provided that answer and became the distinctive point of Israel’s ideology. In the authors’ opinion, “if Israel is not creative in its thinking, there is a chance it will not survive”. Universal conscription allows highly qualified people from different fields to be exposed to the actual needs of the armed forces. Furthermore, Israel’s unique military culture provides space for even junior officers to voice their views and participate in the discussion on important national security issues. According to the authors, mandatory enlistment in Israeli armed forces and breakdown in social hierarchy has created the right environment for promotion of innovation and creativity.